International students’ study-related burnout: Associations with perceptions of the teaching-learning environment and approaches to learning - Yufan Yin; Auli Toom; Anna Parpala (Frontiers in Psychology, 2022)
International students study in new, unfamiliar teaching-learning environments (TLEs) and may thus experience study-related burnout. However, little research exists on the relationship between perceptions of the TLE and such burnout, especially among international students. Nevertheless, one key factor is thought to be students’ approaches to learning. This study investigated the relationship between international students’ perceptions of the TLE, approaches to learning and study-related burnout and how these approaches mediate the relationship between perceptions of the TLE and burnout. The data were collected among international students (n = 162) in a research-intensive Scandinavian university and analyzed using confirmatory factor analyses and structural equation modelling. The results indicated that international students’ study-related burnout correlated negatively with perceptions of the TLE (alignment, interest and relevance, constructive feedback and peer support). Their study-related burnout was positively related to the unreflective approach to learning and negatively related to the deep approach to learning and organized studying. The study proved that approaches to learning acted as mediators between perceptions of the TLE and study-related burnout. The findings indicated that how the dimensions of study-related burnout were affected by different constructs of perceptions of the TLE and approaches to learning among international students. Based on these findings, the study provides implications for improving teaching. Future research should focus on the relationship between the deep approach to learning and exhaustion and how peer support affects study-related burnout.